2019
DOI: 10.1029/2019gl083881
|View full text |Cite
|
Sign up to set email alerts
|

Topographic Shelf Waves Control Seasonal Melting Near Antarctic Ice Shelf Grounding Lines

Abstract: The buttressing potential of ice shelves is modulated by changes in subshelf melting, in response to changing ocean conditions. We analyze the temporal variability in subshelf melting using an autonomous phase‐sensitive radio‐echo sounder near the grounding line of the Roi Baudouin Ice Shelf in East Antarctica. When combined with additional oceanographic evidence of seasonal variations in the stratification and the amplification of diurnal tides around the shelf break topography (Gunnerus Bank), the results su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 64 publications
0
22
1
Order By: Relevance
“…Internal tidal oscillations at subinertial frequencies can therefore only reach the ice shelf as baroclinic Kelvin or topographic Rossby waves that require a vertical wall or sloping bottom, respectively (Gill, 1982). While Sun et al (2019) attributed observed subinertial diurnal oscillations in the basal melt rate along the grounding line of the broad Roi Baudouin Ice Shelf, Antarctica to topographic Rossby waves, we posit that the steep and narrow Petermann Fjord may more likely facilitate baroclinic Kelvin waves. We speculate that the diurnal baroclinic waves are generated by the diurnal barotropic tide traveling across the fjord sill, approximately 65 km seaward of our study site.…”
Section: Discussioncontrasting
confidence: 67%
“…Internal tidal oscillations at subinertial frequencies can therefore only reach the ice shelf as baroclinic Kelvin or topographic Rossby waves that require a vertical wall or sloping bottom, respectively (Gill, 1982). While Sun et al (2019) attributed observed subinertial diurnal oscillations in the basal melt rate along the grounding line of the broad Roi Baudouin Ice Shelf, Antarctica to topographic Rossby waves, we posit that the steep and narrow Petermann Fjord may more likely facilitate baroclinic Kelvin waves. We speculate that the diurnal baroclinic waves are generated by the diurnal barotropic tide traveling across the fjord sill, approximately 65 km seaward of our study site.…”
Section: Discussioncontrasting
confidence: 67%
“…There is an abrupt increase in seafloor depth between the two sites (Horgan et al, ) that may excite diurnal topographic vorticity waves (Mueller et al, ). These tide‐topography interactions may be very sensitive to frequency (e.g., Sun et al, ) and thus may explain Feature 1. However, we would expect to detect these vorticity waves as enhanced diurnal currents at our site, which is less than 1 km away from the topography, given that these waves have slow radiation of energy away from the generating topography.…”
Section: Discussionmentioning
confidence: 99%
“…This ponded water can disrupt the structural integrity of the ice shelf and make it vulnerable to hydrofracturing (Glasser and Scambos, 2008). Basal melt rates close to 0 in winter to 10 m a −1 in summer were observed near in the grounding zone, with large seasonal and tidal variations (Sun and others, 2019). These melt rates are controlled by topographic waves generated at the ice-shelf break.…”
Section: Eastern Dml (24°e To 45°e)mentioning
confidence: 99%